China’s Contribution Through Belt and Road initiative in The New Era - Bella Jastacia (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2023)
In recent years, China's swift economic growth has played a larger role in the global economy. Implemented innovation categories include manufacturing production centers, technological innovation, infrastructure and investment, space exploration, financial technology, the e-commerce revolution, and electric vehicles. China will continue to invest in research and development, high technology, and other strategic sectors to maintain sustainable eco-nomic growth and play a larger role in the global economy in the new era, as a result of the Belt and Road Initiative, which has had a significant impact on the future of the world, such as the construction of infrastructure, education, culture, and also for agriculture.